From Mobilization to Demobilization: Dynamics of Contention in the Austerity-driven Slovenia - Rak, Joanna (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2018)
The article aims to trace the dynamics of contention in austerity-driven Slovenia, explain why it ended, through the processes of demobilization, despite the protest movement’s initial successes, and verify the explanatory power of Charles Tilly and Sidney Tarrow’s theoretical framework of demobilization. The analysis applies the method of source analysis, conceptual qualitative content analysis, and the conceptual framework of contentious politics. In doing so, it addresses the research problems of the dynamics of contention in Slovenia and why the contention resulted in demobilization. The article argues that after mass mobilization an upward scale shift appeared. The shift moved the contention beyond its local origins in Maribor, touched on the interests and values of new subjects, and involved a shift of venue to sites where the demands might have been met by state institutions. The dynamics of contention was a cycle of active and passive contentious episodes. The movement identity shift and successful recognition of its claims influenced the performances and episode sequence. The processes of demobilization started when people stopped attending protests, organizing particular performances, and implementing innovations to modular performances instead. Demobilization occurred when most of the protesters became discouraged from protest through boredom and a desire to return to everyday routines.